IMPLEMENTASI DUPONT SYSTEM DENGAN TIME SERIES APPROARCH (TSA) DAN CROSS SECTIONAL APPROACH (CSA) DALAM PENILAIAN KINERJA KEUANGAN SEKTOR FMCG - sri wahyuti; M. Astri Yulidar abbas; Siti Rohmah; Agus Riyanto; Rio Chandra; Yohanes Christian J. (Jurnal Ekonomika: Manajemen, Akuntansi, dan Perbankan Syari'ah, 2026)
This study implements the DuPont System with Time Series Approach (TSA) and Cross-Sectional Approach (CSA) to assess the financial performance of Fast-Moving Consumer Goods (FMCG) companies listed on the Indonesia Stock Exchange (IDX) from 2020 to 2024. The objective is to evaluate financial performance using the DuPont System under both TSA and CSA frameworks. This research adopts a qualitative descriptive approach, collecting and analyzing company data to provide a comprehensive overview of the subject. Unlike hypothesis-driven studies, descriptive research focuses on presenting variables, phenomena, or conditions as they exist. Data was gathered through secondary sources, primarily from IDX publications, using documentation and literature review methods. Analytical techniques included statistical analysis and hypothesis testing. The analysis results show that PT. Mayora recorded the best performance with an ROE of 104.98% in 2024, supported by the highest TATO (1.62) and moderate leverage increase (EM 2.17). PT. Unilever achieved the highest ROE (155.88%) but with extreme leverage (EM 7.47). Meanwhile, PT. Indofood and PT. Sukses Makmur demonstrated stability with a conservative approach (EM < 2) and low TATO (< 0.6) to enhance ROE. PT. Kalbe Farma experienced performance volatility, with profit surges in 2022 and 2024 but a sharp decline in 2023.